Le double mouvement de l’âme vers l’image: Une théorie aristotélico-thomiste au cœur des débats du milieu du XVIe siècle sur le juste rapport à l’image religieuse - Dekoninck, Ralph (Revue de théologie et de philosophie, 2022)
This article considers a philosophical-theological controversy within the Roman Catholic church which, in the mid-16th c., preceded and foreshadowed the debates that would lead to the preparation of the decree on holy images promulgated at the last (25th) session of the Council of Trent. In particular, it focuses on one of the main points of contention concerning the interpretation of a thesis articulated by Thomas Aquinas, namely a reworking, adapted to another context, of a text by Aristotle. This thesis concerns the type of veneration that should be given to the image, and in particular to that of Christ. The aim of this article is to show how this debate closely intertwines philosophical and theological issues that touch on questions of perception of the image as well as knowledge through the image, simultaneously implying a complex questioning of religious practices.